Prevalence of ear pathologies and associated risk factors in children aged 0-7 years attending Voortrekker Hospital in Mokopane, South Africa - Mabasa, Hlamarisa Vadanile (My University, 2023)
Background: Ear pathologies such as middle ear infections are most common in children (Einhorn, 2017) and if remain untreated they can result in hearing loss which is the most common sensory deficit in the human population (Dawood, Klop, Oliver, Elliott, & Pillay, 2017). Globally, an estimated 34 million children have hearing loss and 60% percent of these childhood hearing loss cases can be prevented or cured, however, the inability to put intervention measures in place can result in apparently more than 900 million people living with hearing loss by the year 2050 (WHO, 2020). There is paucity of literature on factors contributing to ear pathologies in rural areas and therefore, the current study aimed to investigate the prevalence and associated factors for ear pathologies amongst children in a rural area of Limpopo Province. Methods: A retrospective descriptive study was conducted which followed a quantitative approach. This study used secondary data from patient clinical records from a hospital in Limpopo Province. Patients’ records of children 7 years and below that were seen in the audiology department and were registered in the year 2018 January and December 2019 were reviewed. STATA statistical software version 12 for windows was used to analyse. Comparison between groups for continuous and categorical variables was performed using student ttest, and chi-square test, respectively. P-value less than 0.05 at 95% confidence level was regarded as significant. Findings: There was no statistical significant difference between gender (p=0.978) and majority of patients files were in the age group 4 – 7 years at 54.4% followed by those in age group 1 – 3 years and less than 1 year at 37.9% and 7.6% respectively. Majority of the patients were diagnosed with impacted wax 40.6% and males were mostly diagnosed with impacted wax at 43.9% as compared to females at 37.3%. The prevalence of outer ear pathologies was 48.3% followed by prevalence of middle ear at 28.5% while inner ear had only 0.9% and the combined had 4.6%. The prevalence of outer ear pathologies was high in females at 51.2% while the highest prevalence in males was in middle ear pathologies at 32.3%. In overall, for this study, more females than males presented with ear pathologies. Outer ear pathologies were found to be significantly associated with older children, lower respiratory tract infections (LRTI) and those having Moderate Acute Malnutrition (MAM), Severe Acute Malnutrition (SAM), upper respiratory tract infections (URTI) and retroviral diseases (RVD). Middle ear pathologies were found to be significantly associated with older children, parotitis, MAM/SAM, LRTI and RVD. Inner ear pathologies were found to be significantly associated with congenital disorders. Conclusion: More males presented with ear pathologies as compared to females and the prevalence of ear pathologies was high in the current study with outer ear pathologies leading followed by middle era pathologies. The risk factors for ear pathologies were LRTI, URTI, MAM/SAM, RVD, parotitis and congenital disorders. Impacted wax was the most typical diagnosis in both genders while Otitis Media was the least and this could be due to a lack of accessibility and availability of resources for early identification of inner ear disorders.
Thesis (MPH.) -- University of Limpopo, 2023
Keywords: Ear pathologies; Risk factors; Children; Prevalence; Hearing loss; Ear -- Diseases -- Diagnosis; Degeneration (Pathology)